QUALITATIVE REVIEW OF MOSQUE FINANCIAL MANAGEMENT: Implementation of An Accounting System In Controlling Funds - Arianto, Muhammad Rivaldi; Espa, Vitryan; Desyana, Gita (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2024)
This research aims to analyze the implementation of the accounting system in controlling funds in mosques and assess the accountability level in mosque financial management. The open and accountable management of mosque finances is essential to maintaining the congregation’s and stakeholders’ trust. Qualitative methods were used in this research, using a case study approach at the Adda’watul Islamiyah mosque in Pontianak. Data was collected through intense interviews with the mosque committee and direct observation. The research results indicate that effective accounting system practices can improve control of mosque funds, reduce misuse of funds, and increase accountability of mosque committees. Several mosques that use an accounting system in an organized manner and accordance with applicable accounting standards have succeeded in presenting financial reports that are transparent and accountable. This research suggests that the mosque committee implement a more effective accounting system in order to improve control and accountability of mosque funds.